Combined motion of reservoir with liquid for angular motions of carrying body - Limarchenko, Oleg S. (Vietnam Journal of Mechanics, 2009)
We consider peculiarities of the modeling of wave motion of ideal liquid in a reservoir, which performs inclined motions. For description of behavior of the system we use variational formulation of the problem on the basis of the Hamilton-Ostrogradskiy variational principle with preliminary satisfying all kinematic boundary conditions of the problem. It is shown that this approach makes it possible to reduce considerably the number of unknowns of the problem and reduce it description only to parameters of motion of a liquid free surface and parameters of motion of a carrying body. The constructed nonlinear discrete model of the system was applied for investigation of motion of a reservoir with liquid on pendulum suspension, on taking into account liquid outflow and other problems, which have theoretical and applied meaning.